The complexity of calculating an accurate carbonate budget - Dee, S.; Cuttler, M.; O’Leary, M.; Hacker, J.; Browne, Nicola (SPRINGER, 2020)
A carbonate budget is a comprehensive measure of reef health and function that focuses on processes that produce and remove carbonate. A key parameter of a carbonate budget is reef topographic complexity, or rugosity, that is traditionally measured by the chain-and-tape (CT) method. However, to overcome spatial limitations of the CT method, modern studies are moving towards remote sensing data to quantify complexity on a reef-wide scale. Here, we compare rugosity values calculated using the traditional CT method with rugosity values derived from remote sensing, and assess implications of methodological approach for carbonate production estimates. Rugosities derived from remote sensing were calculated from high-resolution (0.1 m) LiDAR bathymetry from two turbid reefs in the Exmouth Gulf, Western Australia, and included virtual chain and tape (VCT), arc–chord ratio (ACR), and surface area to planar area (SAPA). Rugosity values varied significantly between methods (ranges: CT = 1.04–2.15, VCT = 1.01–1.10, ACR and SAPA = 1.00–1.07). Coral carbonate production rates calculated using the CT method were typical of turbid water reefs (2.9 and 3.8 kg m−2 yr−1) which were 30% greater than rates calculated using remote sensing. This variation questions the reliability and comparability of carbonate budgets using remote assessments of reef rugosity with previous budget studies that used the CT method. Given the limitations of remote sensing when capturing fine-scale reef rugosity, we propose that CT is currently a more appropriate method than remote sensing for quantifying rugosity within carbonate budget studies.